[Family Involvement.] - Academy for Educational Development, Washington, DC.; Academy for Educational Development, Washington, DC. ([S.l.] : Distributed by ERIC Clearinghouse, 1996)
This theme issue provides four articles that address family involvement in the transition of youth with disabilities from school to work. The first article, "Family Involvement" by Marge Goldberg and Shauna McDonald, offers evidence of the importance of family involvement at this stage of the individual's life, reports on families' experiences, and notes the value of mentoring families. The second article is "Strategies for Family Involvement," by Marge Goldberg. It provides specific suggestions to parents for getting involved and includes tips from parents to parents and from parents to professionals for the transition years. The third article lists eight national organizations for family involvement. Provided for each organizational listing is address, phone number, World Wide Web site (when available), and a brief description. Also provided are a list of five projects about family involvement (including contact information and a description) and a list of 11 conferences. (DB)
Sponsoring Agency: Office of Special Education and Rehabilitative Services (ED), Washington, DC.
Contract Number: H158M50001.
Practitioners.
Parents.
Alliance: The Newsletter of the National Transition Alliance, v1 n3 Dec 1996.
May also be available online. Address as at 14/8/18
Keywords: Demonstration Programs; Disabilities; Education Work Relationship; Elementary Secondary Education; Family Involvement; National Organizations; Parent Participation; Transitional Programs; Collected Works, Serials; Guides, Non-Classroom.